Study on the mechanism of plant metabolites to intervene oxidative stress in diabetic retinopathy - Gong, Tianyao; Wang, Dongmei; Wang, Jinyan; Huang, Qun; Zhang, Haiyan; Liu, Chunmeng; Liu, Xinglin; Ye, Hejiang (Frontiers in Pharmacology, 2025)
Diabetic retinopathy is the main microvascular complication of diabetes and the first blinding eye disease in the working-age population. Oxidative stress is an important pathogenesis of diabetic retinopathy. Plant metabolites can be divided into two types: primary metabolites and secondary metabolites, secondary metabolites are the main active components and important sources for developing new drugs. It has unique effect in the treatment of diabetic retinopathy. However, the research on the intervention mechanism of plant metabolites in diabetic retinopathy are still relatively shallow, which limit the application of plant metabolites. With the deepening of research, more and more plant metabolites have been reported to play a role in treating diabetic retinopathy through anti-oxidative stress, including polyphenols, polysaccharides, saponins, alkaloids, etc. Therefore, this article reviewed the potential of plant metabolites in the treatment of diabetic retinopathy in the last 10 years and elucidated their mechanism of action. We hope to provide some references for the application of plant metabolites and provide valuable resources for the research and development of new drugs for diabetic retinopathy.